Towards a better assessment of pain and suffering damages for personal injuries : a proposal based on quality adjusted life years / Vaia Karapanou. - Karapanou, Vaia (European studies in law and economics, 2014)
The assessment of non-economic damages associated with personal injury remains a daunting task for courts. It is the subject of a longstanding and unresolved debate in legal scholarship, as it involves an evaluation of the impact of the immaterial loss incurred, for which a satisfactory instrument is currently lacking. Pain and suffering damages are important for compensating the victim, acknowledging the harm suffered and restoring the disturbed peace, and they can also create incentives that have significant economic implications for the decisions of many actors including victims, injurers, insurers, product manufacturers, employers, medical doctors etc. Towards a Better Assessment of Pain and Suffering Damages for Personal Injuries - A Proposal Based on Quality Adjusted Life Years proposes a novel way to assess pain and suffering damages based on specialised scientific information regarding the impact of different types of injuries. Relevant insights from law and economics literature regarding the minimisation of total accident costs are thoroughly discussed and health economics literature is explored in detail with respect to how different types of injuries and other health conditions affect individuals. Attention is also paid to relevant insights from behavioural economics.The book thus provides a comprehensive analysis with respect to current legal rules on pain and suffering damages and assessment approaches in England, Germany, Greece, Italy and the Netherlands, and compares the positive legal and economic implications that would result from the implementation of the proposed framework. The book contributes to the ongoing discussions on tort reform among legal scholars, economists, medical doctors, insurers and legislators. To demonstrate how the proposed framework can be used in practice, pain and suffering damages are assessed for five cases of personal injury and illness (deafness, loss of sight in one eye, paralysis, leg amputation and contraction of HIV-AIDS) and are juxtaposed with the amounts that have actually been awarded by courts for the same type of injuries in England, Germany, Greece, Italy and the Netherlands. By giving straightforward examples of how the proposed framework could be implemented to assess pain and suffering damages based on actual personal injury case law, the book is also of practical value for the judiciary, legal practitioners and policy makers alike.